Evolution of the Four Individual Faculties of Mind within Human Consciousness - Frimpong, Frank Asamoah (Eximia, 2025)
The sequential evolution of the four faculties of mind of the human consciousness is one of the important facts about the human thinking processes that diverse mental theorists and thinkers hinted at but remained fuzzy until now. What psychologists such as Freud, Piaget, and Erickson postulated were stages of development of the physical body as it grows from birth to adulthood similar to Shakespeare’s stages of life. The focus of this research is on the emergence and evolution of each of the four faculties of the human mind based on the historical and evolutionary development of consciousness that differentiated Homo Sapiens from the animal kingdom. There are two recognized stages of development of human consciousness namely, 1) evolution of consciousness based on Darwin’s theory of evolution, and 2) the specific sequential evolution of each of the four faculties of mind of the human consciousness that differentiated human (early Homo Sapiens) consciousness from the consciousness of animals that led to the present sophisticated human thinking system. The development of consciousness started with all animals attaining two faculties of mind namely, Cosmic Consciousness (that works the autonomic systems of the physical bodies of animals), and a faculty of perceptual-mind (that made animals sentient) to be able to feed and avoid being eaten. The next stage of mental development occurred to the present Homo Sapiens who developed a second faculty of imagination that enabled early human beings to make tools of war to subdue wild animals that liberated the cave dwellers to roam the jungles and hunt down animals. The third stage of human mental development was the attainment of the faculty of ego/reason that developed laws and regulations which allowed people to live in cottages and villages. The fourth faculty of mind achieved by human beings was the faculty of superego/conscience that developed principles of morality and fair play for inter-personal relationships, that enabled human beings to live in harmony in larger towns cities and States. This shows the history of the evolution of faculties of mind in ascending order of higher abilities of (each of the four faculties of mind) within human consciousness. In short, this shows the slow sequential stages of evolution of the four faculties of the human consciousness namely, 1) the perceptual-mind, 2) imagination, 3) ego/reason and 4), the superego/conscience, from infancy, to adolescence, adulthood, old age and death.